Lower extremity biomechanics during single-leg drop jump in female basketball players with dynamic knee valgus alignment - Hirokazu Kobayashi; Tomonao Kanamura; Sentaro Koshida; Koji Miyashita; Tsuruo Okado; Takuya Shimizu; Kiyoshi Yokoe (Japanese Society of Physical Fitness and Sports Medicine, 2013)
The objectives of this study were to quantify the contribution of joint motion to dynamic knee valgus and to classify dynamic knee valgus alignment during single-leg jump landing motion in young female basketball players according to the dominant joint motion. Participants were 64 young female basketball players (age 16.1 ± 0.7 years, body mass 58.8 ± 7.8 kg, height 165.4 ± 9.3 cm, and body mass index 21.5 ± 1.8). We collected the motion data with 12 digital video cameras and calculated the knee-in angle and the toe-out angle in the frontal view to select the neutral and dynamic valgus (Knee-in & Toe-out: KI) groups. We also established three-dimensional data of hip, knee, and ankle joint motion. The results demonstrated that the ranges of hip adduction and knee valgus motion were significantly greater in the KI group than in the neutral group (P < 0.0063). In addition, the participants in the KI group were categorized into three different groups: hip dominant type (8 players), knee dominant type (6 players) and foot dominant type (6 players), depending on the dominant relative joint motion for dynamic knee valgus. Our current results suggest that, like other strength training programs, a lower extremity injury prevention program may need to be designed based on detailed kinematic assessment of an individual athlete.